2007
DOI: 10.1111/j.1525-1438.2007.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer in the elderly: feasibility of surgery and chemotherapy in 89 geriatric patients

Abstract: Gynecological oncologists are faced with an increasing proportion of geriatric ovarian cancer patients. Comorbidities are frequently a matter of concern in this age group, and what is adequate treatment for such patients is still debated. The aims of this study were to analyze the feasibility of standard surgery and chemotherapy in a series of elderly ovarian cancer patients (>/=70 years) and to investigate the influence of age (70-75 vs >75 years) on survival. We retrospectively evaluated 89 elderly patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…This corresponds with the results of previous studies (10, 12, 13). However, our data raised a concern that the incorporation of upper abdominal procedures may increase the frequency of specific complications and may cause more physical burden to the elderly patients who underwent EUAS procedures.…”
Section: Discussionsupporting
confidence: 93%
“…This corresponds with the results of previous studies (10, 12, 13). However, our data raised a concern that the incorporation of upper abdominal procedures may increase the frequency of specific complications and may cause more physical burden to the elderly patients who underwent EUAS procedures.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that there might be a group of elderly who could benefit from more aggressive therapy than is offered to them today. Indeed, studies have shown both cytoreductive surgery and combination chemotherapy to be feasible in elderly OC patients [24,25]. More toxicity of TC treatment might be expected in the elderly [26], and several strategies have been described to reduce this problem.…”
Section: Discussionmentioning
confidence: 98%
“…Patients who are perceived to be elderly or frail may receive less aggressive surgery, non-standard chemotherapy regimens, or may be provided less opportunity to participate in clinical trials [4,6,8,12]. For instance, while it is well established that platinum-based adjuvant chemotherapy improves progression-free and overall survival and is therefore standard of care for treatment of EOC [13][14][15][16], elderly EOC patients frequently do not receive standard doublet chemotherapy [8,12,[15][16][17][18][19][20][21][22][23]. Therefore, while intrinsic patient factors contribute to decreased overall survival, there is likely an effect related to differences in patient treatment.…”
Section: Introductionmentioning
confidence: 97%